Missa Je ne menge point de porc - Grabnar, Klemen (De musica disserenda, 2012)
The works of Orlando di Lasso (1530/1532-1594) were widespread across Europe during the second half of the sixteenth and the early seventeenth century. Some of the surviving contemporary sources of music by Lasso - both printed and manuscript - are preserved in Slovenian libraries. Among them are two partially preserved manuscripts, containing his early parody Mass based on the chanson Je ne menge point de porc by Claudin de Sermisy (c. 1490-1562). Lasso's Mass is of special interest due to its use of a thoroughly secular chanson. The reasons for using Sermisy's chanson could be multifaceted - for instance to establish intertextual relationship between the pieces or to compose a short Mass based on a carefully chosen model.
Keywords: Lasso, Orlando di, 1532-1594; "Je ne menge point de porc"; Glasbene študije; živali; svinjina; motivi; vokalna glasba; renesančna glasba